2017
DOI: 10.1108/lodj-03-2015-0052
|View full text |Cite
|
Sign up to set email alerts
|

How change information influences attitudes toward change and turnover intention

Abstract: Purpose The purpose of this paper is to examine how the quality of change information influences employees’ attitude toward organizational change and turnover intention. Additionally, the role of engagement, psychological contract fulfillment and trust in the relationship between change information and attitude toward change is assessed. Design/methodology/approach In a technology services organization that was implementing a “new way of working,” questionnaire data of 669 employees were gathered. The organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 72 publications
3
30
0
Order By: Relevance
“…Several studies have also put emphasis on the role of the motivational base of public sector employees prior to organizational change (Farndale et al, 2011; van den Heuvel et al, 2017). These studies assume that, if employees have positive attitudes toward their organization, they will hold positive views toward organizational change.…”
Section: Theories and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have also put emphasis on the role of the motivational base of public sector employees prior to organizational change (Farndale et al, 2011; van den Heuvel et al, 2017). These studies assume that, if employees have positive attitudes toward their organization, they will hold positive views toward organizational change.…”
Section: Theories and Hypothesesmentioning
confidence: 99%
“…Devos et al (2007) found that, when employment relationships are characterized by high levels of mutual trust, employees are more open to organizational change. In line with van den Heuvel et al’s (2017) argument on the internal context, we focus on the concept of voice climate to describe the internal context in which an organizational change takes place.…”
Section: Introductionmentioning
confidence: 99%
“…Another study confirmed that lack of communication and participants' low involvement during changes were emphasized as important factors, contributing to resistance and that they were related to organizational culture (Canning and Found, 2015). In addition, information about changes was positively related to the psychological implementation of agreements and the attitude to changes (van den Heuvel et al, 2017), as well as to greater confidence, enabling to achieve the set results (Vosse and Aliyu, 2018).…”
Section: Theoretical Backgroundmentioning
confidence: 80%
“…The instrument used for the research was created based on the analysis of scientific literature and by selecting publications using keywords "higher education", "changes", "attitudes of employees" and by focusing on magazines indexed in SCOPUS and WOS databases, which quartile is not lower than Q3. In this way, 15 publications that were published between 2004 and 2018 were selected (Eriksson, 2004;Vakola and Nikolaou, 2005;Alas and Vadi, 2006;Armenakis et al, 2007;Walker et al, 2007;van Emmerik et al, 2009;Stensaker and Meyer, 2011;Hyde, 2012;Carter et al, 2013;Stensaker et al, 2014;Dasborough et al, 2015;Canning and Found, 2015;Fu et al, 2016;van den Heuvel et al, 2017;Vosse and Aliyu, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…This variable was chosen to be used in this research so as to unearth whether change leaders' approach to providing information in the change process affected teachers' attitudes towards change either in a positive or negative way. Research has shown that change-related information is positively associated with attitudes towards change ( Van den Heuvel, Freese, Schalk, & Van Assen, 2017).…”
Section: Are Teachers Informed About the Change Process (Viz The Impmentioning
confidence: 99%